PENGARUH OFFICIAL DEVELOPMENT ASSISTANCE JEPANG TERHADAP PEMBANGUNAN EKONOMI GHANA - Putri Dwi Oktaviani; Yusnarida Eka Nizmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The Purpose  of this research is to mainly inform about the impact of Japan’s ODA (Official Development Assistance ) in promoting the economic  development  of Ghana. The type of Research used by Author  with qualitative Research methode, which is a research procedure that produces descriptive data. Data collection techniques are carried out by library study methods. Research use books, journal, electronic media and various sources that support the research process. The perspective that the author uses is the perspective of liberalism with the level of state analysis, using development theory.This study shows that Ghana is one of African  Sub -Saharan country famous  fo its rich  natural sources that appeals other nations to establish cooperations, in the case Japan. One of the programs initiated  by Japan  is to promote  Ghana’s economic development  is ODA (Official Development Assistance) where Japan  will annually distribute foreign aid to maintain the cooperation between the two countries.Keyword : Ghana, Japan, ODA, Cooperation